Diskriminasi Mitologi Penderita Epilepsi Menurut Kajian Pendidikan Agama Hindu - Anak Agung Gde Oka Widana (Jayapangus Press, 2023)
The purpose of this study is to awaken and straighten out personal perceptions of the existence of people with epilepsy so that mythological discrimination against people with epilepsy can be minimized and eliminated. Three issues are raised in this study: forms of mythological discrimination of epilepsy sufferers, causes of the emergence of mythological discrimination of epilepsy sufferers according to Hindu religious teachings, and solutions in overcoming the phenomenon of mythological discrimination of epilepsy sufferers according to Hindu teachings. As a type of qualitative research, the data obtained in this study were collected using library techniques and document recording. Analysis of the data that has been collected was carried out using a qualitative descriptive technique. The results of the analysis show that the forms of mythological discrimination received by epilepsy sufferers in the Tri Education Center are restrictions, shunned, ostracized, humiliated, humiliated, and even imprisoned. The causes of the emergence of mythological discrimination of people with epilepsy are due to the low quality of education (formal, informal, non-formal), the low implementation of human values, the degradation of morality, and the low implementation of the teachings of Catur Marga Yoga. Solutions that can be taken to overcome the phenomenon of mythological discrimination of epilepsy sufferers according to Hindu religious teachings include improving the quality of tattwa (philosophical) education, increasing moral quality, integrating human values ​​that are integrated in the concept of Pawongan with tat tvam asi, and the last is realizing the implementation of the teachings of catur marga yoga (bhakti marga yoga, jnana marga yoga, karma marga yoga and raja marga yoga).